Fixed Point Theory and Applications - Agarwal, Ravi P.; Nieto, Juan J.; Petrusel, Adrian
In a wide range of mathematical problems the existence of a solution is equivalent to the existence of a fixed point for a suitable map. The existence of a fixed point is therefore of paramount importance in several areas of mathematics and other sciences. Fixed point results provide conditions under which maps have solutions. The theory itself is a beautiful mixture of analysis (pure and applied), topology, and geometry. Over the last 50 years or so the theory of fixed points has been revealed as a very powerful and important tool in the study of nonlinear phenomena. In particular, fixed point techniques have been applied in such diverse fields as biology, chemistry, economics, engineering, game theory, and physics. The aim of this journal is to report new fixed point results and their applications in which the indispensability of the fixed point results is highlighted. This journal will accept high quality articles containing original research results and survey articles of exceptional merit. An article to be published in Fixed Point Theory and Applications must contain either some new applications to real world problems or reveal novel aspects of the theory applicable to new situations.